Current Status in the Treatment of Acute Cholecystitis Patients Receiving Antithrombotic Therapy: Is Endoscopic Drainage Feasible?- A Systematic Review - Ryota Sagami; Kenji Hayasaka; Hidefumi Nishikiori; Hideaki Harada; Yuji Amano (Korean Society of Gastrointestinal Endoscopy, 2020)
The bleeding complication risk of surgery or percutaneous transhepatic gallbladder drainage (PTGBD) may increase in patients with acute cholecystitis receiving antithrombotic therapy (ATT). Endoscopic gallbladder drainage (EGBD) may be recommended for such patients. English articles published between 1991 and 2018 in peer-reviewed journals that discuss cholecystectomy, PTGBD, and EGBD in patients with ATT or coagulopathy were reviewed to assess the safety of the procedures, especially in terms of the bleeding complication. There were 8 studies on cholecystectomy, 3 on PTGBD, and 1 on endoscopic transpapillary gallbladder drainage (ETGBD) in patients receiving ATT. With respect to EGBD, 28 studies on ETGBD (including 1 study already mentioned above) and 26 studies on endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) were also analyzed. The overall bleeding complication rate in patients with ATT who underwent cholecystectomy was significantly higher than that in patients without ATT (6.5% [23/354] vs. 1.2% [26/2,224], p<0.001). However, the bleeding risk of cholecystectomy and PTGBD in patients receiving ATT was controversial. The overall technical success, clinical success, and bleeding complication rates of ETGBD vs. EUS-GBD were 84% vs. 96% (p<0.001), 92% vs. 97% (p<0.001), and 0.65% vs. 2.1% (p=0.005), respectively. One patient treated with ETGBD experienced bleeding complication among 191 patients with bleeding tendency. ETGBD may be an ideal drainage procedure for patients receiving ATT from the viewpoint of bleeding, although EUS-GBD is also efficacious.